Changing practice in dementia care in the community: developing and testing evidence-based interventions, from timely diagnosis to end of life (EVIDEM) - Steve Iliffe; Jane Wilcock; Vari Drennan; Claire Goodman; Mark Griffin; Martin Knapp; David Lowery; Jill Manthorpe; Greta Rait; James Warner (NIHR Journals Library, 2015)
Background: The needs of people with dementia and their carers are inadequately addressed at all key points in the illness trajectory, from diagnosis through to end-of-life care. The EVIDEM (Evidence-based Interventions in Dementia) research and development programme (2007-12) was designed to help change this situation within real-life settings. Objectives: The EVIDEM projects were (1) evaluation of an educational package designed to enhance general practitioners' (GPs') diagnostic and management skills; (2) evaluation of exercise as therapy for behavioural and psychological symptoms of dementia (BPSD); (3) development of a toolkit for managing incontinence in people with dementia living at home; (4) development of a toolkit for palliative care for people with dementia; and (5) development of practice guidance on the use of the Mental Capacity Act (MCA) 2005. Design: Mixed quantitative and qualitative methods from case studies to large database analyses, including longitudinal surveys, randomised controlled trials and research register development, with patient and public involvement built into all projects. Setting: General practices, community services, third-sector organisations and care homes in the area of the North Thames Dementia and Neurodegenerative Diseases Research Network local research network. Participants: People with dementia, their family and professional carers, GPs and community mental health team members, staff in local authority social services and third-sector bodies, and care home staff. Main outcome measures: Dementia management reviews and case identification in general practice; changes in behavioural and psychological symptoms measured with the Neuropsychiatric Inventory (NPI); extent and impact of incontinence in community-dwelling people with dementia; mapping of pathways to death of people with dementia in care homes, and testing of a model of collaborative working between primary care and care homes; and understandings of the MCA 2005 among practitioners working with people with dementia. Results: An educational intervention in general practice did not alter management or case identification. Exercise as a therapy for BPSD did not reduce NPI scores significantly, but had a significant positive effect on carer burden. Incontinence is twice as common in community-dwelling people with dementia than their peers, and is a hidden taboo within a stigma. Distinct trajectories of dying were identified (anticipated, unexpected and uncertain), and collaboration between NHS primary care and care homes was improved, with cost savings. The MCA 2005 legislation provided a useful working framework for practitioners working with people with dementia. Conclusions: A tailored educational intervention for general practice does not change practice, even when incentives, policy pressure and consumer demand create a favourable environment for change; exercise has potential as a therapy for BPSD and deserves further investigation; incontinence is a common but unrecognised problem for people with dementia in the community; changes in relationships between care homes and general practice can be achieved, with benefits for people with dementia at the end of life and for the UK NHS; application of the MCA 2005 will continue to improve but educational reinforcements will help this. Increased research capacity in dementia in the community was achieved. This study suggests that further work is required to enhance clinical practice around dementia in general practice; investigate the apparent beneficial effect of physical activity on BPSD and carer well-being; develop case-finding methods for incontinence in people with dementia; optimise working relationships between NHS staff and care homes; and reinforce practitioner understanding of the MCA 2005. Trial registration: EVIDEM: ED-NCT00866099; EVIDEM: E-ISRCTN01423159. Funding: This project was funded by the Programme Grants for Applied Research programme of the National Institute for Health Research.